Dhikr Therapy: Overcoming Life Anxiety with Islamic Counseling Based on QS Ar-Ra'd Verse 28 - Indriani, Tiya; Jarkawi, Jarkawi; Ridhani, Akhmad Rizkhi (Letiges, 2024)
This research aims to conduct a literature review regarding the effectiveness of dhikr-based Islamic counseling in overcoming life anxiety based on the Al-Qur'an Surah Ar-Ra'd verse 28. The literature research method applied is statements and checklists, using the